Research on Design of the D-knotter Split Spindle - Guo, Jiayu; Cen, Haitang; Tang, Hao; Shuang, Zihan; Na, Risu (Journal of physics. Conference series, 2022)
The knotter is the core component of the square baler. The structure of the knotter is complex, the working load is large and the working environment is bad, which makes the knotter easily damaged. The imported D-knotter is widely used at present, once the parts are damaged, they often need to be disassembled and assembled as a whole, which takes a long time and seriously affects the efficiency of field operation. Aiming at the problem that the D-knotter assembly and its parts are inconvenient to replace after damage, this paper designs the split spindle of the knotter, and ensures the strength requirements of the spindle when working through an integral key connection. When replacing the knotter parts, the spindle is separated from the middle, and the knotter assembly is directly removed without removing other parts on the spindle, which obviously saves the replacement time of the damaged parts of the knotter. The statics and modal analysis show that the split spindle of the knotter can meet the strength requirements, and the spindle does not produce resonance.